Translation, validation and psychometric properties of the Albanian version of the Nurses Professional Competence Scale Short form - Duka, Blerina; Stievano, Alessandro; Caruso, Rosario; Prendi, Emanuela; Ejupi, Vlora; Spada, Florian; De Maria, Maddalena; Rocco, Gennaro; Notarnicola, Ippolito (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The primary aim of this study was the translation and psychometric validation of the Albanian Nurse Professional Competence Scale Short Form (A-NPCS-SF) for further application in Albanian healthcare settings. Methods: The multiphase design used to develop the A-NPCS-SF comprised (1) cultural and linguistic validation, (2) content and face validity, and (3) construct validity. Results: The A-NPCS-SF showed adequate content validity. Confirmatory factor analysis supported the six-factor structure of the A-NPCS-SF to explain the data obtained from the nurses. Conclusions: The A-NPCS-SF showed evidence of validity and reliability in measuring four professional competencies. Having an appropriate scale in Albanian for professional competence self-assessment by nurses constitutes an essential step in measuring these competencies. (www.actabiomedica.it)